(untitled) (American Journal of Islam and Society, 2008)
Books Reviewed: Philip Jenkins, God’s Continent: Christianity, Islam, and Europe’s Religious Crisis. Oxford and New York: Oxford University Press, 2007; Jane Idleman Smith, Muslims, Christians, and the Challenge of Interfaith Dialogue. Oxford and New York: Oxford University Press, 2007; Irfan A. Omar, ed., A Muslim View of Christianity: Essays on Dialogue by Mahmoud Ayoub. Maryknoll, New York: Orbis, 2007. Not surprisingly, the Archbishop of Canterbury’s recent comments about integrating more of Shari`ah law within the United Kingdom’s legal system raised a firestorm of protest in Britain and in many parts of the world. Yet for twenty-five years already, Britain’s Muslims have been using Shari`ah law in community arbitration; by simply adding elements of Islamic jurisprudence in family matters, Muslims would be able to settle most divorce cases through arbitration, thus freeing up already congested divorce courts. Why is this suggestion so outrageous? The only explanation for the deluge of complaints has to do with the super-charged and dangerously polarized socio-cultural and religious atmosphere of the “West” in the 2000s. Besides 9/11, other events have contributed to the ratcheting-up of Muslim-European tension: the Danish cartoon saga; the assassination of Dutch filmmaker Theo Van Gogh; the London bombings; the “Fitna” film; and, most recently, the tendentious DVD distributed to nearly 30 million American households in swing states during the presidential campaign, “Obsession: Radical Islam’s War Against the West.” With right-wing politicians determined to raise the specter of “Islamofascism,” any mention of including aspects of the Shari`ah in “enlightened” secular legal structures is enough to give some people fits of panic. Yet this is the context in which we must insert the three books under review, each of which examines a particular aspect of today’s vastly complex Muslim-Christian relationship. Philip Jenkins marshals his consider ...